NUMERICAL INVESTIGATION OF COLD-FORMED STEEL HOLLOW STRUCTURAL SECTIONS DUE TO COMBINED AXIAL COMPRESSION AND BENDING LOADS - Budiman Budiman; Mohammad Imamuddin; Basit Al Hanif; Hendras Duwi Handoyo (University Muhammadiyah Jakarta, 2023)
old-formed steel has emerged as a prominent material in modern construction due to its excellent structural performance, cost-effectiveness, and sustainability. Hollow structural sections made of cold-formed steel have garnered significant attention due to their favourable strength-to-weight ratios and versatility in construction applications. In this research, the cross-section of cold-formed steel hollow structural sections will be analysed as a structure that receives a combination of compressive and bending loads. Numerical analysis was carried out using the finite element method with the help of ABAQUS software to obtain the buckling behaviour and cross-sectional capacity. The cold rolled steel regulations in SNI 79712013 or AS/NZS 4600 will be compared with numerical results to see the level of performance of the code in the case of hollow structural sections. Numerical testing and cross-sectional capacity calculations refer to existing references in the literature.